The first mitochondrial genome of Codonobdella sp. (Hirudinea, piscicolidae), an endemic leech species from Lake Baikal, Russia and reassembly of the Piscicola geometra data from SRA - Alexander Bolbat; Ekaterina Matveenko; Elena Dzyuba; Irina Kaygorodova (Mitochondrial DNA. Part B. Resources, 2021)
In this study, we assembled a complete mitochondrial genome of Codonobdella sp. sample from Lake Baikal, Russia and reassembled third party raw data of Piscicola geometra. Mitogenomes of both freshwater piscine leeches consist of 37 genes, including 13 protein-coding genes (PCGs), two ribosomal genes (12S and 16S), 22 transport RNA genes, and one control region. The complete mitogenome of Codonobdella sp. is 14,486 bp long and A + T biased (75.51%). The complete mitogenome of Piscicola geometra is 14,788 bp long and A + T biased (78.27%).